Perceived TMT transformational leadership and a service recovery culture: the moderating role of gender diversity. Issue 8 (23rd September 2020) - Galbreath, Jeremy; Hoffman, Douglas; Gonzalez, Gabriel; Quaddus, Mohammed
Abstract : Purpose: This is an exploratory study with the purpose of empirically testing and advancing knowledge on the relationship between top management team (TMT) leadership styles and a service recovery culture. A further test explores a contingency perspective, examining if gender diversity on the TMT shapes this relationship. Design/methodology/approach: We examine the perceived TMT transformational leadership style, as well as the moderating effect of TMT gender diversity. Relying on both survey and archival data, our hypotheses are tested with a sample of 234 public firms based in the United States. Moderated hierarchical regression analysis is used as the statistical approach. Findings: Results suggest that perceived TMT transformational leadership is positively associated with a service recovery culture. When accounting for TMT gender diversity, the relationship between perceived TMT transformational leadership and a service recovery culture is positively moderated. Research limitations/implications: The study represents a sample of for-profit public firms operating in the United States and should not be taken as a general population sample. The findings could vary relative to other countries, private companies and non-profit organizations. Originality/value: This is the first known study to explore the relationship between TMT leadership styles, TMT gender diversity and a service recovery culture. The study extends findings with the respect to the impact of TMT leadership and gender diversity on organizational development, as well as offers new insights into the antecedents of a service recovery culture.